2006
DOI: 10.1097/01.shk.0000194719.82845.39
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Endotoxin-Induced Oxidative Stress and Multiple Organ Injury by 3,4-Methylenedioxyphenol in Rats

Abstract: Endotoxin is a potent inducer of lipid peroxidation (LPO), which is associated with the development of endotoxemia. 3,4-Methylenedioxyphenol (sesamol) is one of the sesame oil lignans with a high anti-LPO effect. Whether sesamol can attenuate endotoxin-induced LPO and multiple organ injury is unknown. After a dose response for sesamol in endotoxin-challenged rats was established, experiments were conducted to assess its effects on hydroxyl radical, peroxynitrite, and superoxide anion counts, activities of supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 32 publications
1
46
0
1
Order By: Relevance
“…Sesame oil contains phenol, sesamin, sesamol, sesamolin, and a relatively small amount of tocopherol, which contributes to its superior oxidative stability [21]. Sesamol is a nonfat antioxidant in sesame oil [22]; it is effective against drug-induced and chemically induced organ injuries [23,24]. The anti-MMP-9 [25], anti-inflammatory [26][27][28], antioxidant [29][30][31], and anti-injury, and wound healing [32,33] properties of sesamol contribute to the therapeutic efficacy of sesamol against disease models.…”
Section: Introductionmentioning
confidence: 99%
“…Sesame oil contains phenol, sesamin, sesamol, sesamolin, and a relatively small amount of tocopherol, which contributes to its superior oxidative stability [21]. Sesamol is a nonfat antioxidant in sesame oil [22]; it is effective against drug-induced and chemically induced organ injuries [23,24]. The anti-MMP-9 [25], anti-inflammatory [26][27][28], antioxidant [29][30][31], and anti-injury, and wound healing [32,33] properties of sesamol contribute to the therapeutic efficacy of sesamol against disease models.…”
Section: Introductionmentioning
confidence: 99%
“…Polymicrobial sepsis and organ dysfunction are associated with immunosuppression, a predominance of proinflammatory cytokines, including TNF-␣ and IL-6, as well as a profound loss of lymphocytes via apoptosis (3, 4, 7-9, 19, 25). In addition, various toxins are released from bacteria during sepsis, which serve to further promote cytokine release, vasodilation, oxidative damage, and subsequent cardiovascular collapse (13,17,23,27).Previous studies from our group have demonstrated that endotoxin induces left ventricular contractile dysfunction, and that certain chemical reagents, including p38 MAPK inhibitors and heat shock protein, can reduce this dysfunction (22, 29). Furthermore, endotoxin preconditioning has been shown to protect cardiac tissue, and it appears that estrogen and the MAPK pathways play a role in this mechanism (2,15,24,30).…”
mentioning
confidence: 99%
“…Polymicrobial sepsis and organ dysfunction are associated with immunosuppression, a predominance of proinflammatory cytokines, including TNF-␣ and IL-6, as well as a profound loss of lymphocytes via apoptosis (3, 4, 7-9, 19, 25). In addition, various toxins are released from bacteria during sepsis, which serve to further promote cytokine release, vasodilation, oxidative damage, and subsequent cardiovascular collapse (13,17,23,27).…”
mentioning
confidence: 99%
“…Широко используемое в традиционной тайваньской медицине кунжутное масло при приеме внутрь в опыте на крысах, которым индуцировали приступ подагры путем инъекций кристаллов моноурата натрия, в сравнении с контролем снижало суммарное количество клеток в лаваже из очага воспаления и в окружающих тка-нях, в том числе лейкоцитов и нейтрофилов, активирован-ных тучных клеток, уровни фактора некроза опухоли α (ФНОα), интерлейкина 1β (ИЛ1β) и ИЛ6, белков системы комплемента С3а и С5а; снижалась активность ФНОα и ИЛ4 в тучных клетках [53]. Причиной может быть сеза-мол -органическое производное фенола, обладающее противовоспалительным и антиоксидантным эффектами [54][55][56].…”
Section: мясо и морепродук тыunclassified